2007
DOI: 10.1007/s12038-007-0038-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of insulin resistance

Abstract: Free fatty acids are known to play a key role in promoting loss of insulin sensitivity, thereby causing insulin resistance and type 2 diabetes. However, the underlying mechanism involved is still unclear. In searching for the cause of the mechanism, it has been found that palmitate inhibits insulin receptor (IR) gene expression, leading to a reduced amount of IR protein in insulin target cells. PDK1-independent phosphorylation of PKCε causes this reduction in insulin receptor gene expression. One of the pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 67 publications
(55 reference statements)
0
62
0
Order By: Relevance
“…Insulin resistance (IR) is defined as a state of reduced responsiveness of tissues to insulin, despite its normal or elevated concentration in blood; the disorder mainly occurs in adipose tissue, skeletal muscle cells, and liver (Bhattacharya et al 2007;Frank & Tadros 2014). The consequences of IR include impaired glucose uptake by the tissues, increased efficiency of gluconeogenesis, and increased lipolysis (Treiber et al 2006).…”
Section: Mechanisms Of Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance (IR) is defined as a state of reduced responsiveness of tissues to insulin, despite its normal or elevated concentration in blood; the disorder mainly occurs in adipose tissue, skeletal muscle cells, and liver (Bhattacharya et al 2007;Frank & Tadros 2014). The consequences of IR include impaired glucose uptake by the tissues, increased efficiency of gluconeogenesis, and increased lipolysis (Treiber et al 2006).…”
Section: Mechanisms Of Insulin Resistancementioning
confidence: 99%
“…Insulin transduces signals into cells through specific insulin receptors ( Figure 1). Insulin receptors are present on the surface of nearly all cells, but most are found on the surface of striated muscle cells, liver cells, and adipocytes (Bhattacharya et al 2007;Rojek & Niedziela 2009;Ye 2013). …”
Section: Introductionmentioning
confidence: 99%
“…PKC phosphorylation is dependent on PDK1; FFA incubation of skeletal muscle cells and adipocytes inhibited PDK1 phosphorylation but surprisingly increased PKC phosphorylation. Inhibition of PDK1 by FFA is reflected in Akt phosphorylation as Akt phosphorylation is also dependent on PDK1 [161]. It has been shown that myristic acid incubation of HEPG2 cells causes myristoylation of PKC which results in constitutive phosphorylation of PKC at thr566/ser729 in the kinase domain required for PKC activity.…”
Section: Ffa Induced Inhibition Of Insulin Receptor (Ir) Gene Expressmentioning
confidence: 99%
“…With the advancements in high throughput screening, proteomics, genomics, molecular docking, and combinatorial chemistry, new therapeutic entities are being developed that influence enzyme activities, signaling receptors and pathophysiological pathways [1,2] . Modern day quantitative structural activity relationship and docking studies are enabling development of bio-active molecules that can achieve structural modifications and thereby alter their pharmacological actions and pharmacokinetic profile so as to maximize bioavailability and minimize the side effects [4][5][6][7][8][9][10] . Latest anti-diabetic drug development pipeline focuses on pharmacological targets which include receptors and enzymes that will increase insulin sensitivity, intracellular insulin signaling, enhance peripheral utilizations of glucose, suppress hepatic glucose production and reduce the levels of circulating tri glycerides [4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%